Segovia y los orígenes de la imprenta española - De los Reyes Gómez, Fermín (Revista General de Información y Documentación, 2005)
Segovia is the first town which possessed a press, brought by bishop Juan Arias Dávila in order to print texts to serve the clergy of the General Stodium. In charge was the German Printer Juan Párix, who worked out at least eight editions between 1472 an 1474/5, date in which he settled in Toulouse: One of his works, the Sinodal de Aguilafuente, in sonsiderd to be the first Spanish printed book. Althought most of this is well known to the scholars, this item presents some new data of the beginning of the press in Segovia backing the presence here of Juan Párix, destined to the wide world of librazianship and Information Sciences.
Keywords: Origin of print; Segovia; Juan Párix; Juan Arias Dávila; Sinodal Aguilafuente; Roma; Ulrich Han